2022
DOI: 10.1097/cm9.0000000000002164
|View full text |Cite
|
Sign up to set email alerts
|

Burden of pancreatitis and associated risk factors in China, 1990 to 2019: a systematic analysis for the Global Burden of Disease Study 2019

Abstract: Background: Pancreatitis is a common disease of the digestive system. Acute pancreatitis is one of the most common reasons for gastrointestinal hospital admission, and chronic pancreatitis significantly reduces quality of life. However, national epidemiological data on pancreatitis in China are lacking. This study aimed to quantify the disease burden of pancreatitis in China from 1990 to 2019. Methods: This study was based on the Global Burden of Disease Study 2019 dataset. Age-standardized rates of incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…A 10-year retrospective study from China found that the estimate number of death caused by alcoholinduced AP was 3327.29 in 2019. Meanwhile, the disease burden caused by alcohol use was most serious among young and middle-aged male, reaching the highest value in the age group of 35 to 54 [28]. In our study, the average age in RAP group was 49.69 years, which was consistent with the above results.…”
Section: Discussionsupporting
confidence: 91%
“…A 10-year retrospective study from China found that the estimate number of death caused by alcoholinduced AP was 3327.29 in 2019. Meanwhile, the disease burden caused by alcohol use was most serious among young and middle-aged male, reaching the highest value in the age group of 35 to 54 [28]. In our study, the average age in RAP group was 49.69 years, which was consistent with the above results.…”
Section: Discussionsupporting
confidence: 91%
“…GBD data show an upward trend in SDI in China, increasing from 0.456 in 1990 to 0.707 in 2017. Since 2003, China's SDI has exceeded the global average (37). The increase observed in the annual incidence and number of patients over the 30-year period of this study may be explained by advances in TC diagnosis as well as the increase in the total population in China.…”
Section: Discussionmentioning
confidence: 65%
“…East Asia, South Asia, and Western Europe had the highest cases [ 6 ]. According to a meta-analysis study, the global incidence of acute pancreatitis (AP) was 33.74, and those of chronic pancreatitis (CP) were 9.62 per 100,000 population per year [ 7 ]. The mortality in patients with AP was 1.60/100,000, and mortality in patients with CP was 0.09/100,000.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality in patients with AP was 1.60/100,000, and mortality in patients with CP was 0.09/100,000. In 2019, it was estimated that the global incidence, disability-adjusted life years, and pancreatitis patient mortality were 34.8/100,000 and 1.4/100,000, respectively [7]. Several studies have demonstrated that AP patients may eventually develop chronic symptoms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%